Strategi Meningkatkan Kualitas Pendidikan Melalui Kualifikasi Akademik Dan Kompetensi Profesional - Joni Joni (Institut Agama Islam Hidayatullah Batam, 2025)
Improving the quality of education is a crucial aspect of creating superior and competitive human resources. One of the main strategies for realizing quality education is by strengthening the academic qualifications and professional competence of educators. This study aims to examine the relationship between academic qualifications, the professional competence of teachers, and the improvement of the quality of education. This study uses literature study methods and qualitative descriptive analysis. The results of the study indicate that efforts to improve the quality of education include certification, ongoing training, performance evaluation, relevant curriculum, mentoring, learning technology, and policy support. The formation of professional groups and the provision of awards are also important. However, there are obstacles such as limited resources, access to training, management support, inadequate policies, high workloads, and suboptimal infrastructure and technology.